Temporal trends in the incidence and outcomes of shock-refractory ventricular fibrillation out-of-hospital cardiac arrest - Abdulrahman Alhenaki; Zainab Alqudah; Brett Williams; Emily Nehme; Ziad Nehme (Resuscitation Plus, 2024)
Aim: We aimed to describe trends in the incidence and outcomes of refractory ventricular fibrillation (RVF) compared to non-refractory ventricular fibrillation (non-RVF) in out-of-hospital cardiac arrest (OHCA). Methods: Between 2010 and 2019, we included all OHCA cases involving adults ≥ 16 years old with an initial shockable rhythm and who received an attempted resuscitation by Emergency Medical Services (EMS) or a bystander shock prior to EMS arrival in Victoria, Australia. Trends in incidence and survival outcomes over the study period were examined. Adjusted logistic regression analyses were conducted to examine factors associated with RVF, as well as the association of RVF on survival to hospital discharge. RVF refers to patients receiving three or more consecutive shocks without a return of spontaneous circulation (ROSC). Results: Of the 57,749 OHCA attended by EMS, 7,267 met the inclusion criteria. Of these, 4,168 (57.4%) were non-RVF and 3,099 (42.6%) were RVF. The incidence of RVF decreased significantly from 7.7 per 100,000 population in 2010 to 5.6 per 100,000 population in 2019 (p-trend = 0.01). Survival to hospital discharge increased significantly for both the RVF and non-RVF groups (26% vs 41% in 2010 to 31% vs 53% in 2019, p-trend = 0.004 for RVF; and p-trend = 0.01 for non-RVF). Compared to non-RVF, RVF was associated with reduced odds of survival to hospital discharge (Odds Ratio = 0.503 [95% confidence interval 0.448 – 0.565]). Factors associated with a lower likelihood of RVF and improved survival to hospital discharge included being witnessed to arrest by EMS, receiving bystander defibrillation and bystander cardiopulmonary resuscitation (CPR). Conclusion: The incidence of RVF is declining, and survival rates are improving. Early treatment of VF patients with bystander CPR and defibrillation is likely to reduce RVF incidence.